Purification and Properties of Thermostable Fucoidanase Produced by Recently Isolated Terrestrial Aspergillus flavus FS018: Characteristics of fucoidanase extracted from Aspergillus flavus FS018 - Garuba, Emmanuel O.; Adeleye, Paul A.; Onilude, Abiodun A. (Trends in Peptide and Protein Sciences, 2020)
In this study fucoidanase produced by terrestrial Apsergillus flavus FS018 was purified and characterized. The pure fucoidanase enzyme was found to have an optimum activity of 20.8U/mL at 55 ºC and optimum activity of 17.2U/mL at pH 5.0. Furthermore, the fucoidanase retained 96% of its activity after 8 hours of incubation at 55 ºC. Metal ions such Mg2+ and Ca2+ ions were found to slightly enhance the activity of this enzyme while Na+, K+ had inhibitory effect on the activity. The enzyme was found to be active towards fucoidan consisting of α-1→4 and α-1→3 glycoside bonds in the main chains and also galactofucans group. Estimation of the kinetic parameters of the enzyme revealed that Km and Vmax to be 1.9 mM and 0.38 mg/min, respectively when fucoidan from Sargassum vulgare was used as substrate. SDS-PAGE analysis of the purified enzyme revealed that it’s a monomeric enzyme molecule with an estimated molecular weight of 70 kDa. HIGHLIGHTS Fucoidanase from Aspergillus flavus FS018 was purified and characterized. Molecular weight of the enzyme was estimated to be 70kDa. Enzyme was active towards fucoidan consisting of α-1→4 and α-1→3 glycoside bonds in the main chains and also galactofucans group.